A Prebiotic Formula Improves the Gastrointestinal Bacterial Flora in Toddlers. (14th June 2016) - Chen, Ya-Ling; Liao, Fang-Hsuean; Lin, Shyh-Hsiang; Chien, Yi-Wen
Abstract : We aimed to investigate the effect of enriched 3-prebiotic formula (including inulin, fructooligosaccharides, and galactooligosaccharides) on toddler gut health by measuring fecal microbiota. Our results revealed that the consumption of 3-prebiotic formula three times per day giving total intake of 1.8 g prebiotic ingredients significantly showed the increased number of probiotic Bifidobacterium spp. colonies and the reduced populations of both C. perfringens and total anaerobic bacteria on the fecal bacterial flora in toddlers at 18~36 months. In addition, total organic acids in the fecal samples significantly increased which improves the utilization of bifidus under acidic conditions after consumption of the 3-prebiotic formula. Therefore, using the formula enriched with prebiotic may maintain gut health in toddlers.